2018
DOI: 10.3390/rs10070997
|View full text |Cite
|
Sign up to set email alerts
|

Using 250-M Surface Reflectance MODIS Aqua/Terra Product to Estimate Turbidity in a Macro-Tidal Harbour: Darwin Harbour, Australia

Abstract: Turbidity is an indicator of the quality of water and usually exhibits variability associated with changing hydrodynamic conditions, which can be reflected in the sediment dynamics in coastal regions. Darwin Harbour is a typical macro-tidal, well mixed, and complex environment influenced by industries, human activities, and natural factors-including winds, currents, river discharges, waves, and tides. As a case study, hydrodynamics and sediment dynamics in Darwin Harbour are investigated using moderate resolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…For modeling coastal water quality in terms of turbidity, we have used a Semi-Analytic Sediment Model (SASM), which was already applied to MODIS Aqua observations (Dorji et al 2016). Recently SASM model has used by (Yang et al 2018) using MODIS Terra observations and found that this model performed better than other linear and exponential models (Dorji and Fearns 2017). Algorithms of the SASM model used in the present study are explained as following (Eq.…”
Section: Modeling Coastal Marine Water Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…For modeling coastal water quality in terms of turbidity, we have used a Semi-Analytic Sediment Model (SASM), which was already applied to MODIS Aqua observations (Dorji et al 2016). Recently SASM model has used by (Yang et al 2018) using MODIS Terra observations and found that this model performed better than other linear and exponential models (Dorji and Fearns 2017). Algorithms of the SASM model used in the present study are explained as following (Eq.…”
Section: Modeling Coastal Marine Water Qualitymentioning
confidence: 99%
“…Ozone Monitoring Instrument (OMI) (Latif et al 2021) and Sentinel-5 Precursor Tropospheric Monitoring Instrument (TROPOMI) were recently missioned to map air pollution worldwide. Surface Reflectance data from MODIS onboard Aqua/Terra sensors at 250 m resolution and daily temporal scale provide a better understanding of the coastal marine water quality (Yang et al 2018). Herein, the effects of ongoing restricted anthropogenic activities on the atmospheric NO 2 are investigated based on real-time observations from the OMI satellite by comparing NO 2 in 2020 with the average of past years (2015 À 2019).…”
Section: Introductionmentioning
confidence: 99%
“…TSM retrieval was carried out using 645 nm (Red) data after applying geo-referencing and atmospheric corrections as suggested by [8], [21], [22]. This data is highly useful for studying turbid coastal waters as the measurements in these bands do not saturate in turbid waters [23], [24].…”
Section: Datamentioning
confidence: 99%
“…Various TSM retrieval algorithms were developed using the relation between MODIS reflectance measurements and in-situ observations for different regions of the world [3], [8], [30] - [33]. In the study region, TSM retrieval algorithm was developed based on MODIS single band reflectance in the red region (λ = 645nm) and the available in-situ observations through regression based best-curve fit method and is given as follows:…”
Section: A Calibration Of Tsm Retrieval Algorithmmentioning
confidence: 99%
See 1 more Smart Citation